2015
DOI: 10.1002/ajpa.22758
|View full text |Cite
|
Sign up to set email alerts
|

Across language families: Genome diversity mirrors linguistic variation withinEurope

Abstract: Objectives: The notion that patterns of linguistic and biological variation may cast light on each other and on population histories dates back to Darwin's times; yet, turning this intuition into a proper research program has met with serious methodological difficulties, especially affecting language comparisons. This article takes advantage of two new tools of comparative linguistics: a refined list of Indo‐European cognate words, and a novel method of language comparison estimating linguistic diversity from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 65 publications
(102 reference statements)
2
43
0
1
Order By: Relevance
“…Although grammar data are not currently available for the populations we sampled, recent studies have found a strong association between genes and grammar data for populations within Europe56 and across Europe, Africa, and Western Asia57. It has previously been hypothesized3458 that grammatical rate of change is more comparable to the rate of change of some genetic systems than to that of others, which has been partly supported for a sample of populations from Eurasia and Africa57.…”
Section: Discussionmentioning
confidence: 53%
“…Although grammar data are not currently available for the populations we sampled, recent studies have found a strong association between genes and grammar data for populations within Europe56 and across Europe, Africa, and Western Asia57. It has previously been hypothesized3458 that grammatical rate of change is more comparable to the rate of change of some genetic systems than to that of others, which has been partly supported for a sample of populations from Eurasia and Africa57.…”
Section: Discussionmentioning
confidence: 53%
“…Unfortunately, these results say little about the within-group variance in culture relative to genes. Other studies have shown parallels in the patterns of linguistic and genetic diversity (Perreault and Mathew, 2012; Longobardi et al, 2015; Creanza et al, 2015; Hunley et al, 2008), but again provided no information about the ratio of genetic to cultural variance. However, this question is well-suited to empirical study; given our results, empirical estimates of the ratio can shed light on qualitative expectations about the evolution of behavioral traits.…”
Section: Discussionmentioning
confidence: 94%
“…It is a plausible guess that as syntax should be free from the arbitrariness of lexical meanings, it should also be less directly influenced by the variability of culture. Of course, if we find that genetic diversity and syntactic diversity are measurably correlated with each other in a significant way (Longobardi et al 2015), without there being direct causation between the two variables, then it is possible that differences in other cultural features (say, laws, culinary traditions etc.) may also interestingly correlate with language diversity.…”
Section: What Are the Main Advantages / Reasons To Study Linguistic Vmentioning
confidence: 88%